PENGARUH KOMPETENSI LEADERSHIP GURU PENDIDIKAN AGAMA ISLAM TERHADAP KECERDASAN KOMUNIKASI INTERPERSONAL PESERTA DIDIK SMPN 1 ENREKANG - Mutmainnah Amin, Rizqy; Azis, Rosmiaty; Yahdi, Muhammad (Jurnal Pendidikan Kreatif, 2021)
This research aims to; 1) Describe the teacher leadership competency of Islamic Education at SMPN 1 Enrekang; 2) Describe the intelligence of interpersonal communication of students at SMPN 1 Enrekang; 3) Describe the influence of Islamic Religious Education teacher leadership competencies on the interpersonal communication intelligence of students at SMPN 1 Enrekang. This type of research is a post-facto quantitative study with a simple linear regression research design. This research was conducted at SMPN 1 Enrekang. The population in this study were 257 students at SMPN 1 Enrekang. While the samples in this study were 57 people using the simple random sampling method. The research instrument used to obtain data is the scale of leadership competence and interpersonal intelligence scale. The data analysis technique used is descriptive statistical analysis and inferential analysis. Based on the results of the descriptive statistical analysis the results of the leadership competency study of Islamic Religious Education teachers at SMPN 1 Enrekang are in the medium category, which is 88.37%, while the results of interpersonal communication intelligence of students at SMPN 1 Enrekang are in the medium category, namely 73.96% . From the calculation results obtained (tcount) = 2.835 while (ttable) = 2.004 for a significance level of 0.05%. Because it is greater than it can be concluded that H0 is rejected and H1 is accepted. This means that there is an influence of Islamic religious education teacher leadership competencies on students' interpersonal communication intelligence at SMPN 1 Enrekang.